Studi Tentang Pengawasan dan Lingkungan Kerja serta Pengaruhnya Terhadap Kinerja Pegawai - Sonjaya, Yana; Ambarsari, Megie; Marnoto, Marnoto; Julaeha, Ela (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
This research aims to identify the extent to which the work environment and supervision influence employee performance. The research method employed is quantitative analysis. The research population consists of 360 employees of a Private Bank in Bandung. A sample of 72 individuals was taken, equivalent to 20% of the total population. Data were analyzed using SPSS 22.0 software, including reliability testing, validity testing, multiple linear regression analysis, F-test, and determination coefficient (R2) test. The results of the analysis indicate that the work environment and supervision collectively influence employee performance. The percentage of the influence of the work environment and supervision on employee performance, according to the results of the determination coefficient (R2) test, is an adjusted R Square value of 29.2%, while the remaining 70.8% is influenced by other factors not examined.